"J" is for Judgment - Grafton, Sue.; Random House Audio Publishing ([New York] : Random House Audio, 1993)
While investigating the reappearance of the long-presumed-dead Wendell Jaffe, Kinsey Millhone uncovers some unpleasant truths about her own family in the process.
Compact disc
"A Kinsey Millhone Mystery"--Container.
Abridged.
Read by Judy Kaye.
Keywords: Millhone, Kinsey (Fictitious character) -- Fiction; Women private investigators -- Fiction -- California; Audiobooks (Abridged); California -- Fiction; Mystery fiction